HR and PR as an effective business-communications (Herald of Journalism, 2020)
The main idea of an article is an actual development of the most pro- ductive ways of cooperation of HR and PR in structure of organization.
Keywords: Public Relations, Human Resources, business-communica- tions, cooperation of structure subdivision.